Modern аpproaches to designing student dormitories: energy efficiency, functionality, and social environment (Международный научный журнал «Инженер», 2026)
This article analyzes contemporary trends in the design of student dormitories aimed at meeting students' needs for comfortable, safe, and energy-efficient environments. The study explores the principles of functional-compositional analysis of spatial-planning solutions and their adaptation to changes in the educational environment and social demands. Special attention is given to international experience in designing student dormitories, which has allowed for the identification of best practices in sustainable construction and the creation of a comfortable educational environment. In conclusion, recommendations are provided for improving the design solutions of student dormitories in Uzbekistan, considering the specific local climatic and economic conditions.